Hydrogeochemical Analysis to Identify Potential Groundwater Characteristics in the Jayapura Region - Felice Deglardini Wopari; Rusmawan Suwarman; Irwan Iskandar (OPHIOLITE: Jurnal Geologi Terapan, 2025)
Hydrogeochemistry and stable isotope δ18O and δ2H are chemical methods used to understand the chemical process of water flows in the aquifer. This study aims to identify the characteristics of groundwater and surface water in the Jayapura area.  Water samples are collected from 87 points throughout the study area. The results of hydrogeochemical analysis on the main ions presented in the piper diagram show that the dominant water type is Ca/Mg-HCO₃-. In addition, other water types such as Ca-HCO₃-, Na-HCO₃-, Mg-SO42-, Ca-Cl, and Na-Cl are found. Rainwater is used as the reference line in the diagram, referred to as LMWL (local meteoric water line), with the equation H = 7.019δ18O + 7.5162 and a correction coefficient of 0.997. Stable isotope analysis of δ18O and δ2H in groundwater and surface water shows that most of the water is within the range of the LMWL reference line. There are two points above the LMWL reference line with Ca-Cl water type. The result of this study indicated that the characteristics of water resources in the Jayapura area are influenced by the interaction between water and mineral weathering near the surface. This interaction provides a natural and good water resource potential in the region.